Calculation Algorithm for Diffraction Losses of Multiple Obstacles Based on Epstein–Peterson Approach - Ahmad S. Abdulrasool; Jabir S. Aziz; Sadiq J. Abou-Loukh (International Journal of Antennas and Propagation)
Applying propagation models with good accuracy is an essential issue for increasing the capacity and improving the coverage of cellular communication systems. This work presents an algorithm to calculate total diffraction losses for multiple obstacles objects using Epstein–Peterson approach. The proposed algorithmic procedure to model the diffracting can be integrated with other propagation mechanisms in ray-tracing for the prediction of received signal level in non-line-of-sight environments. This algorithm can be interpreted into software application to scan large areas with a reasonable simulation time.